2012
DOI: 10.4236/health.2012.410133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutritional intake in US adolescent swimmers and non-athletes

Abstract: Swimming is a very popular sport among adolescents in the US. Little is known about the diet of competitive adolescent swimmers in the US but data from other countries indicate several inadequacies, including excessive intake of fat and lower than recommended intake of carbohydrate and several micronutrients that may affect athletic performance and bone accrual. We assessed usual diet, using a food frequency questionnaire and calcium checklist, among 191 adolescent males and females [91 swimmers (mean 13.7, s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…All found that sport participants had higher FV intake than non-sport participants, but no specific cup equivalents were reported. Others have examined the FV intake of youth athletes, including swimmers (1.6–2 cups/day) and rugby players (1.3 cups/day) [ 34 , 35 ], but no comparison group was included. Finally, Parnell et al [ 36 ] compared the FV intake of Canadian youth athletes to the Canadian diet recommendations for teens and found 40–54% met the FV guidelines of 7–8 servings per day.…”
Section: Discussionmentioning
confidence: 99%
“…All found that sport participants had higher FV intake than non-sport participants, but no specific cup equivalents were reported. Others have examined the FV intake of youth athletes, including swimmers (1.6–2 cups/day) and rugby players (1.3 cups/day) [ 34 , 35 ], but no comparison group was included. Finally, Parnell et al [ 36 ] compared the FV intake of Canadian youth athletes to the Canadian diet recommendations for teens and found 40–54% met the FV guidelines of 7–8 servings per day.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber intake is often low in the diet of athletes. Several studies, involving female artistic gymnastics, rhythmic gymnastics and ballet dance athletes (88), or competitive American adolescent swimmers (89) reported that athletes' fiber consumption was often below the nutritional guidelines of 25 g per day (based on a 2,000-calorie diet) (90). Only a few studies reported fiber consumption above the nutritional guidelines, and one of the few examples is female and male Dutch ultramarathon runners (91).…”
Section: Diet Can Modulate the Microbiome And Gut Health Of Endurance Athletesmentioning
confidence: 99%
“…W pracy Collins i wsp. [18] także nie stwierdzono istotnych różnic pomiędzy nastoletnimi pływakami a młodzieżą nietrenującą w zakresie spożywania produktów zbożowych, nabiału, warzyw i owoców. Badania ankietowe, przeprowadzone na grupie ponad 100 polskich pływaków z Pomorza w wieku 12-14 lat ujawniły znaczne odstępstwa od prawidłowego schematu żywienia.…”
Section: Omówienieunclassified